EAI International Conference on Technology, Innovation, Entrepreneurship and Education TIE'2017 - Reyes-Munoz, Angelica; Zheng, Ping.; Crawford, David; Callaghan, Victor; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the proceedings of the 1st EAI International Conference on Technology, Innovation, Entrepreneurship and Education (TIE 2017), which took place at Canterbury Christ Church University on September 11-12, 2017. The central theme of the conference is creativity and innovation, especially in relation to technology, business, education, social and political needs that make modern society flourish. The proceedings feature papers from a cross-disciplinary audience that explore the process of creativity and innovation. The goal is that the various disciplines can learn from each other and see how they might benefit from the cross-fertilization of practices.
Introduction -- Big Data, the Internet of Things and Smart Cities Research: A Literature Review and Research Agenda -- B2C relationship quality on sharing economy under Chinese context -- Improving Higher Education Quality in Jordan using Mobile Technologies for Better Socio-economic Diversity Integration of Disadvantaged Groups using a Mobile Multimedia /Augmented Reality workflow -- Holonovel: Perspective on Enactive Narrative Intelligence -- A Scenario Centred Approach to Emotion Profiling based on EEG Signal Processing -- A Responsive Templating Approach for Generating Collaborative Spaces -- A Study of Digital Science Fiction Prototyping in an Elementary School Setting -- CSF Dream Academy: Using Fiction, Cardboard and Simple Electrical Circuits as Educational Tools to Lift Disadvantaged Children Out of the Poverty Trap -- Using a Creative Science Approach for Teaching English as a Foreign Language to Postgraduate Students -- Developing the Business Process Management Performance of an Information System Using the Delphi Study Technique -- Logistic Model Based Evaluation of Anti-Counterfeiting Effectiveness for Consumer Goods -- Idea validation for an acceleration program connected with equity based crowdfunding -- Omni-channel Service Architectures in a Technology-based Business Network: An Empirical Insight -- Science Fiction Prototypes Illustrating Future Digital See-Through Structures in Mobile Work Machines -- Teaching Creativity in the Context of a Business School -- Enhancing Student Retention and Engagement within Higher Education -- Educating Responsible Innovators-to-be: Hands-on Participation with Biotechnology -- Smart Enhanced Context-Aware for Flipped Mobile Learning: SECA-FML -- Designing interactive tools for learning in the digital age -- Semantic-based Search Engine System for Graph Images in Academic Literature -- A Low-Cost Portable Health Platform for the Monitoring of Human Physiological Signals -- ICT Technologies that are Essential to Smart Cities Dimensions -- Creating Content for Educational Testing Using a Workflow that Supports Automatic Item Generation -- Alternative Learning Experiences: An Innovative Project Stimulating Creative faculty of Humanities Students -- The shape of firms: opportunities from rapid manufacturing -- Conclusion.
Keywords: Telecommunication; Computer networks .; Technological innovations; Entrepreneurship; New business enterprises; Communications Engineering, Networks; Computer Communication Networks; Innovation and Technology Management; Entrepreneurship